Corporate social responsibility, country reputation and corporate reputation: A perspective on the creation of shared value in emerging markets. Issue 2 (15th July 2019) - Kelley, Keith James; Hemphill, Thomas A.; Thams, Yannick
Abstract : Purpose: This paper aims to explore the relationship between corporate social responsibility (CSR) and corporate financial performance (CFP) from a shared value perspective. Adopting reputation as a multilevel form of value that mediates the CSR–CFP relationship, the paper explains how CSR initiatives may enhance both firm and country reputation and how the amount of shared value between the two leads to CFP. Design/methodology/approach: The paper first establishes the theoretical foundation for the relationship between CSR and CFP. It then draws connections to a more recent stream of literature surrounding the concept of creating shared value to expand upon this relationship, adopting reputation as a multilevel form of shared value that mediates the CSR–CFP relationship. The paper further discusses moderating influences of this relationship that may vary contextually with emerging economies such as those in Latin America. Findings: The paper argues that as markets become further developed, CSR initiatives will create a higher proportion of shared reputational value between a corporation and country. This is the result of from aligning CSR initiatives that benefit a society, with the strategic goals of the firm – the essence of creating of shared value – but is more difficult in emerging markets, especially volatile ones. Originality/value: This paper offers insight into a complex relationship between CSR, shared reputational value and CFP by introducing the more recent concept of creating shared value. Several propositions related to this general relationship, and some related to the difference among emerging markets (such as those in Latin America), address the need for more research related to corporate and country reputation, creating shared value and in the emerging market context.